Daily Suction Provided by External Volume Expansion Inducing Regeneration of Grafted Fat in a Murine Model. Issue 2 (February 2017) - Ye, Yuan; Liao, Yunjun; Lu, Feng; Gao, Jianhua
Abstract : Background: Fat grafting has variable and sometimes poor outcomes, and therefore new methods are needed. Multiple studies have demonstrated the excellent performance of external volume expansion and focused only on preexpansion with emphasis on the recipient. Methods: Two mouse models (a suction model and a fat-exchange transplantation model) were established to investigate changes in the origins and biological behaviors of regeneration-related cells in grafted fat under daily suction provided by external volume expansion. Results: Blood supply increased from new host-derived capillaries or macrophage infiltration under suction. CD34-positive cells showed increased migration from the host into the grafts under suction. At week 12, nearly half of the mature adipocytes regenerated in the grafts in the suction group were derived from the host. Peroxisome proliferator-activated receptor γ expression of the suction group was significantly higher than that of controls at weeks 2 and 4 during adipogenesis. The normalized sample weight of the grafted fat was significantly greater than that of controls at 1 (0.081 ± 0.001 versus 0.072 ± 0.005; p < 0.001), 4 (0.060 ± 0.002 versus 0.048 ± 0.001; p = 0.002), 8 (0.060 ± 0.001 versus 0.046 ± 0.001; p < 0.001), and 12 weeks (0.060 ± 0.001 versus 0.046 ± 0.001; p = 0.002). Conclusions: The mechanical effect of daily suction provided by external volume expansion favors the regeneration of grafted fat and improves retention by promoting the migration of regeneration-related cells and the differentiation of adipocytes. Thus, more mature fat tissue with a well-organized structure was formed under suction. Abstract : Supplemental Digital Content is available in the text.